2018
DOI: 10.1002/mnfr.201800824
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of a High Dose of Vitamin D or Its Combination with Sulforaphane on Intestinal Inflammation and Tumorigenesis in Apc1638N Mice Fed a High‐Fat Diet

Abstract: Scope The previous study shows that obesity‐promoted inflammation is responsible for the activation of the intestinal tumorigenic Wnt‐signaling. The present study aims to test a dietary strategy, dietary supplementation with a high dose of vitamin D (VD) or its combination with sulforaphane (SFN) to inhibit intestinal inflammation and obesity‐associated tumorigenesis. Methods and results Apc1638N mice are randomly divided into four groups: LF, a low‐fat diet (10 kcal% fat) with 200 IU VD; HF, a high‐fat diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…For instance, anchor-dependent cell aberration induces autophagy and entosis as well as anoikis [40,41]. Vitamin D and sulforaphane, functional lipids from food, enhance autophagy in small intestine tissue in APC 1638N mice given a high-fat diet [42]. Nintedanib, a tyrosine kinase inhibitor, is suggested to induce entosis in human prostate cancer cells in xenografted mice, along with E-cadherin upregulation and CDC42 downregulation [43].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, anchor-dependent cell aberration induces autophagy and entosis as well as anoikis [40,41]. Vitamin D and sulforaphane, functional lipids from food, enhance autophagy in small intestine tissue in APC 1638N mice given a high-fat diet [42]. Nintedanib, a tyrosine kinase inhibitor, is suggested to induce entosis in human prostate cancer cells in xenografted mice, along with E-cadherin upregulation and CDC42 downregulation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D alone did not induce autophagy in DU145 and PC-3 cells, but it increased autophagy rates when combined with sulforaphane at 4 µM and 8 µM, respectively. The sulforaphane–vitamin D combination induces autophagy in the small intestine of mice [ 24 ]. Our findings suggested that vitamin D potentiated the effect of sulforaphane in inducing autophagy-associated cell death in DU145 and PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D combined with sulforaphane can modulate the WNT signaling pathway and inhibit histone deacetylases in Caco-2 colorectal cancer cells and TMX2–28 breast cancer cells [ 55 , 56 ]. This nutraceutical combination also induces autophagy in Apc1638N mice, which is heterozygous for germline mutation in the Apc gene and used to study intestinal tumorigenesis [ 24 ]. The findings of the present study with achievable plasma concentrations corroborate those described in the literature regarding the anticancer potential of sulforaphane and vitamin D in combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two test groups are presented as without (−) and with (+) SFN since that is the only differing factor between HFD and HFDS dietary groups. Details of the sample collection and preservation are discussed elsewhere 19 …”
Section: Methodsmentioning
confidence: 99%